A Small Field, High Resolution γ-Camera System dedicated to SPECT Imaging - Thanasas, D.; Georgiou, E.; Giokaris, N.; Karabarbounis, A.; Maintas, D.; Mikeli, M.; Papanicolas, C. N.; Stiliaris, E. (HNPS Advances in Nuclear Physics, 2020)
A small field, high resolution γ-Camera system dedicated to radiopharmaceutical research and other clinical SPECT (Single Photon Emission Computed Tomography) applications is currently being developed in our group. The system is equipped with the 3” HAMAMATSU R2486 Position Sensitive PhotoMultiplier Tube (PSPMT) with a 16X+16Y-crossed wire anode and various pixelated and ho- mogeneous scintillation crystals. Planar images are created from the recorded charge signals by applying the resistive chain technique. The main part of this work focuses on the development of new correction methods for the improvement of the spatial resolution and the uniformity of the γ-Camera. The spatial distortion correction technique is based on lookup tables with the coordinates of reference points which are selected during the calibration phase of the system for a given set of collimator and scintillation crystal. The applied algorithm incorporates 2D-interpolation tech- niques and has been developed on a full automated graphics environment making use of the HIGZ (High Level Interface to Graphics and ZEBRA) program libraries from CERN. Both correction methods for the spatial distortion and non-uniformity have been applied to phantom images using several combinations of small capillaries filled with water solution of 99mTc. Comparative studies are shown on planar im- ages for different phantom geometries. The method is also extended to tomographic images and the obtained SPECT improvement in resolution is discussed.